2013
DOI: 10.1136/bcr-2013-008905
|View full text |Cite
|
Sign up to set email alerts
|

Organising pneumonia in common variable immunodeficiency

Abstract: Common variable immunodeficiency (CVID) is the most common of the primary immunodeficiency disorders. Pulmonary manifestations are characterised by recurrent rhinosinusitis, respiratory tract infections and bronchiectasis. Less commonly the lung may be affected by lymphoid disorders and sarcoid-like granulomas. Organising pneumonia (OP) is a rare pulmonary manifestation. We report the case of a 32-year-old woman with CVID who presented with fever, dyspnoea and persistent lung infiltrates despite antibiotic the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Treatment with glucocorticoids led to a partial response in 13% (four individuals) and failed to maintain remission in 7% (two individuals) of patients (18,29). There are, however, also literature reports about the positive effects of glucocorticoids (16,17,20,21). 23% (seven individuals) of all patients using glucocorticoids had resolution of symptoms.…”
Section: Not Mentionedmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with glucocorticoids led to a partial response in 13% (four individuals) and failed to maintain remission in 7% (two individuals) of patients (18,29). There are, however, also literature reports about the positive effects of glucocorticoids (16,17,20,21). 23% (seven individuals) of all patients using glucocorticoids had resolution of symptoms.…”
Section: Not Mentionedmentioning
confidence: 99%
“…Ten additional studies included glucocorticoid treatment as one of several therapies (Tables 2 and 3). Five of these reported no effect of glucocorticoids (26,27,31,(36)(37)(38), one reported relapse after initial remission (29) and four reported treatment success (16,17,20,21). The article by Kanathur et al is particularly interesting as it describes a case in which glucocorticoids initially failed to have any effect at all but FIGURE 2 | Comparison of the available qualitative and quantitative outcomes of studies that reported on patients (N) treated with steroids, rituximab monotherapy and rituximab combination therapy.…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…Organising pneumonia, formerly known as bronchiolitis obliterans organising pneumonia, has been described as a frequent presentation in PADs [93][94][95][96][97]. It is a nonspecific reactive inflammation resulting from different causes of epithelial lung injury (infections, inflammation and fibrosis) and characterised by plugs of granulation tissue and spirals of fibroblasts, known as Masson bodies, in the alveolar spaces [16,98].…”
Section: Asthma and Copdmentioning
confidence: 99%
“…6,13-15 Additionally, granulomatous lung disease is found in many cases 16-18 and organizing pneumonia (OP) in some. 19-21 Granulomatous-lymphocytic interstitial lung disease (GLILD) has been used as an encompassing term for this combination of pathologic findings in CVID. 6 …”
Section: Introductionmentioning
confidence: 99%